Plasma turbulence, suprathermal ion dynamics and code validation on the basic plasma physics device TORPEX. (13th March 2015) - Furno, I.; Avino, F.; Bovet, A.; Diallo, A.; Fasoli, A.; Gustafson, K.; Iraji, D.; Labit, B.; Loizu, J.; Müller, S. H.; Plyushchev, G.; Podestà, M.; et al.
Abstract : The TORPEX basic plasma physics device at the Center for Plasma Physics Research (CRPP) in Lausanne, Switzerland is described. In TORPEX, simple magnetized toroidal configurations, a paradigm for the tokamak scrape-off layer (SOL), as well as more complex magnetic geometries of direct relevance for fusion are produced. Plasmas of different gases are created and sustained by microwaves in the electron-cyclotron (EC) frequency range. Full diagnostic access allows for a complete characterization of plasma fluctuations and wave fields throughout the entire plasma volume, opening new avenues to validate numerical codes. We detail recent advances in the understanding of basic aspects of plasma turbulence, including its development from linearly unstable electrostatic modes, the formation of filamentary structures, or blobs, and its influence on the transport of energy, plasma bulk and suprathermal ions. We present a methodology for the validation of plasma turbulence codes, which focuses on quantitative assessment of the agreement between numerical simulations and TORPEX experimental data.